Development of a law library consortium in Metro Manila - Jaafar, Tadz Majal Ayesha V. (2012)
It is an established fact that no library is complete and can give everything to its clients. The reasons behind this include the continuously rising costs of library resources and services, information explosion, and advances in technology, among others. To ensure that the information needs of the clients are satisfied, consortia are formed, wherein the libraries can share resources and services. In the Philippines, consortia and networks have been proven to be effective in addressing the above-mentioned concerns. No consortium, however, was formed for law libraries. There are only informal arrangements among law librarians. Thus, this study proposes a model for a law library consortium in Metro Manila and a Memorandum of Agreement.